A fault confessed is half redressed: The impact of deviant workplace behavior on proactive behavior - Sen Zhang; Mengru Zhao (Administrative Sciences, 2024)
The extant research on deviant workplace behavior has mainly examined the consequences of such behavior from a "victim-centric" perspective, while ignoring the psychological and behavioral responses of the employees who engaged in it. Drawing upon moral cleansing theory, we adopt a "victimizer-centric" perspective and contend that employees experience moral deficits after engaging in deviant workplace behavior, which consequently lead to subsequent proactive behavior. We also propose that the indirect relationship between deviant workplace behavior and proactive behavior is contingent upon individuals' moral courage. Specifically, employees with high moral courage are more inclined to perform subsequent proactive behavior upon perceiving a moral deficit than those with low moral courage. Our hypotheses are supported by empirical data from an experimental study involving 128 participants in the United Kingdom (Study 1) and a multi-wave survey-based field study with a sample of 180 employees conducted in the United States (Study 2). Our research provides contributions to the literature on deviant workplace behavior by demonstrating how and when deviant workplace behavior can lead to subsequent compensatory behavior, as well as practical insights for both employees and organizations.
Keywords: 350; deviant workplace behavior; moral cleansing; moral courage; moral deficit; proactive behavior